La The philosophy of engineering in the context of the formation of the engineer (2013)
The process of research, development and innovation in the area of engineering is confined to the technological scientific context dominated by physics, chemistry, geology, mathematics and other sciences derived from these basic principles of generating this knowledge science. In this sense they should be considered the following characteristics; know how attitude particular man and his environment, and retrieved in various ways including particular experience and academic formality, which brings us to the context of epistemological and scientific knowledge as objective of knowledge whose particularity is the intrinsic strength in being which allows you to analyze your potential, science whose purpose is the articulate laws for understanding various phenomena and whose medium is the fixation of knowledge for verification of this. Not only scientific knowledge is defined according to its reference scientific genesis, but it is confined to his discipline of knowledge; in this sense, it is necessary to discern in the epistemological and philosophical location of each science in order to define your method. To develop new applications or theoretical knowledge in the area of engineering, it is necessary to use appropriate tools belonging to these domains of knowledge, almost always to the hand of the developments of physics, chemistry and other sciences, so that the new advances and developments occur in the light of the developments of the sciences which have been generated.